Multi‐wavelength Pulse Amplitude Modulated fluorometry (Phyto‐PAM) reveals differential effects of ultraviolet radiation on the photosynthetic physiology of phytoplankton pigment groups. (19th October 2016) - Beecraft, Laura; Watson, Sue B.; Smith, Ralph E. H.
Summary: The effects of UV‐B, UV‐A and PAR on the photochemistry of phytoplankton from Hamilton Harbour, Lake Ontario, were measured to assess how well a multi‐wavelength Pulse Amplitude Modulated fluorometer (Phyto‐PAM) could discriminate among different pigment groups and to test whether bloom‐forming cyanobacteria in this embayment have comparatively high resistance to sunlight stress. Estimates of abundance for the three groups (blues, greens and browns) identified by the Phyto‐PAM generally agreed with microscope counts, but the maximum quantum efficiency of photochemistry ( F v : F m ) was usually quantified only for the dominant group. In acute exposure experiments, the average inhibition of F v : F m by PAR, UV‐A and UV‐B was <10, 30 and 60% respectively. More inhibition was observed in the cyanobacteria compared to the eukaryotic phytoplankton, due to higher rates of photosystem damage rather than lower rates of recovery based on the Kok model for photoinhibition. Both F v : F m and photosynthetic carbon incorporation showed similar patterns of inhibition. Based on F v : F m our results showed no evidence that cyanobacteria are more resistant to UVR stress compared to other groups, however, their success as bloom‐forming species suggests they must have other mechanisms to tolerate if not thrive under high irradiance conditions. These results demonstrate both the utility and limitations of the Phyto‐PAM for the assessment of group‐specific abundance and physiological responses in a natural community: general seasonal and inter‐group variation can be captured, but improved resolution of less abundant groups would enhance its application.